2009
DOI: 10.14742/ajet.1179
|View full text |Cite
|
Sign up to set email alerts
|

Usability and usefulness of eBooks on PPCs: How students' opinions vary over time

Abstract: <blockquote><p>The number of academic eBooks in university libraries is increasing. Reading digital materials such as newspapers is valued in Hong Kong; however, students' perceptions of the value of reading academic eMaterials are not well known. In this study we investigated 12 students' use of academic eBooks on mobile readers in two ways. Six students had brief introduction to eBooks and they reported their first impressions of the technology. The other six students had a 12-week eBook reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 9 publications
1
68
0
8
Order By: Relevance
“…Un grupo recibió una introducción al dispositivo de lectura y luego fueron motivados para que comentasen sus primeras impresiones de la tecnología. Mientras tanto, el segundo grupo participó en un experimento de seguimiento de 12 semanas de duración, en el que la lectura digital realizada fue supervisada por los investigadores (Lam et al 2009) y fue, en cierto modo, similar a la realizada en Territorio Ebook. Entre los resultados obtenidos por la investigación es importante resaltar la visión de los investigadores en percibir que los dispositivos de lectura electrónica tienen el potencial de ser utilizado para el aprendizaje y la enseñanza, sin embargo, todavía hay varias dificultades que superar.…”
Section: Lectores En La Nube: 19 Y 39 Añosunclassified
“…Un grupo recibió una introducción al dispositivo de lectura y luego fueron motivados para que comentasen sus primeras impresiones de la tecnología. Mientras tanto, el segundo grupo participó en un experimento de seguimiento de 12 semanas de duración, en el que la lectura digital realizada fue supervisada por los investigadores (Lam et al 2009) y fue, en cierto modo, similar a la realizada en Territorio Ebook. Entre los resultados obtenidos por la investigación es importante resaltar la visión de los investigadores en percibir que los dispositivos de lectura electrónica tienen el potencial de ser utilizado para el aprendizaje y la enseñanza, sin embargo, todavía hay varias dificultades que superar.…”
Section: Lectores En La Nube: 19 Y 39 Añosunclassified
“…But performance gains are often obstructed by learners' unwillingness to accept and use available system [21,22]. The studies by Davis (1989), Liaw (2008), Lam (2009), Shroff (2011) explored variables such as perceived usefulness, perceived ease of use, attitudes towards usage and behavioral intention to use that may influence system use [23][24][25][26]. In addition, among the variables that may influence system use, previous research suggests learner's perceived usefulness and perceived ease of use that are especially important [27][28][29][30][31][32].…”
Section: Perceived Usefulness and Perceived Ease Of Use That Affectinmentioning
confidence: 99%
“…However, performance gains are often obstructed by learners' unwillingness to accept and use available systems [5,6]. Among the variables that may influence system use, many previous research suggested that learner' s perceived usefulness and perceived ease of use play importance roles in effecting the usage of technology system [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Siendo capaces, ahora, de enviar, almacenar, editar y leer documentos en un soporte diferente al papel. (LAM et al, 2009;ASHCROFT, 2011).…”
Section: Introductionunclassified